COMPARISON OF ANTIBACTERIAL ACTIVITY OF Curcuma longa AND Curcuma zedoaria RHIZOMES EXTRACTS AT A CONCENTRATION OF 12.5% AGAINST Streptococcus mutans - Martha Mozartha; Muhammad Yusuf Diansyah; Listia Eka Merdekawati (Journal of Health and Dental Sciences, 2021)
Streptococcus mutans is a microorganism that important in dental caries. Herbs are known to have antibacterial activity against oral bacteria. The rhizomes of Curcuma longa and Curcuma zedoaria are two of the eight species of genus Curcuma that are most widely used as traditional herbal medicine in Indonesia. Both rhizomes have antibacterial activity against oral bacteria at a concentration of 12.5%. This study aimed to examine the inhibitory of Curcuma longa and Curcuma zedoaria rhizomes extracts against the growth of Streptococcus mutants. The study was in vitro study. Both rhizomes got from the Experimental Garden of Balittro Manoko Lembang, West Java, Indonesia. The maceration was employed to obtain the extracts with the final extracts of both rhizomes at a concentration of 12.5%. Antibacterial activity test was carried out by using the agar well diffusion method. The positive control group was 0.2% Chlorhexidine and distilled water as a negative control group. The data obtained were then analyzed using the One Way ANOVA Test and Post Hoc Test. Results showed that chlorhexidine 0.2% had the largest mean diameter of the inhibition zone. Curcuma longa rhizome extract had a larger mean diameter of inhibition zone compared to Curcuma zedoaria rhizome extract. However, the difference in the mean values of the two rhizomes extracts was not statistically significant. Distilled water didn't have antibacterial activity. It can be concluded that both Curcuma longa and Curcuma zedoaria rhizomes extracts at a concentration of 12.5% have antibacterial activity against Streptococcus mutans. DOI : 10.54052/jhds.v1n2.p175-187